COPD prevalence and characteristics in a random sample of workers - Stoleski, Sasho; Minov, Jordan; Mijakoski, Dragan; Atanasovska, Aneta; Bislimovska, Dragana (European Respiratory Society, 2024)
COPD is a global public health problem, causing a very high rates of morbidity, mortality, and work disability in the last decades worldwide. Objective. To determine the prevalence and characteristics COPD in a random sample of workers form the city of Skopje, and its relation to occupational exposures. Methods: A cross-sectional study was conducted including 1.867 workers (959 males and 908 females) from the city of Skopje. Afterwards, the study subjects were divided into exposed (1.287/68.9%) and unexposed (580/31.1%) groups based on their current job exposure to noxious particles and gases. All study participants completed a questionnaire and underwent pre- and post-bronchodilator spirometry. Results: COPD prevalence was 3.9% among all workers. COPD prevalence in exposed workers was significantly higher compared to unexposed (4.7% vs. 2.4%). Significant difference was found in exposed workers with exposure duration longer than 20 years as compared to those with shorter duration of exposure (6.0 vs. 3.2%). COPD prevalence in workers who smoked was significantly higher than in non-smoking workers in both exposed (6.0% vs. 3.9%, (P = 0.037)) and unexposed (3.9% vs. 1.8%, (P = 0.000)) groups. The difference between workers with COPD in terms of use of solid and liquid bio fossil fuels at home and central heating/electricity is not significant (5.0% vs. 3.6%), both in exposed (5.4% vs. 4.3%), as well as non-exposed workers (3.8% vs. 1.9%). Conclusions: Our findings confirmed the role of occupational exposures in COPD development indicating a need of more effective preventive activities in order to reduce the overall disease burden.